2019
DOI: 10.1155/2019/3867874
|View full text |Cite
|
Sign up to set email alerts
|

Research on Taxi Pricing Model and Optimization for Carpooling Detour Problem

Abstract: This paper builds a multiobjective optimization model for solving the taxi carpooling with detour problem and designs a genetic algorithm to determine a fair pricing scheme for riders and drivers. The researches show that it is feasible to share a taxi with detour. It is the key to determine appropriate carpooling payment ratio and detour carpooling payment ratio. The ratio of detour distance to travel distance has an important influence on detour carpooling. It should be limited to less than certain values. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The optimization of matching participants, routes, and schedules is widely and actively studied, as shown in Table 5. Several algorithms have been proposed to overcome traditional problems like passenger to driver matching [66] to minimize time and distance to the carpooling starting point and destination [67], to find participants within organizations [68], to determine the pricing schemes for the driver and the passengers [67], and to plan the route by integrating different means such as public transportation or bike rentals with carpooling [69]. Several studies examine the business models framework for services in smart cities.…”
Section: Literature Collection #1mentioning
confidence: 99%
“…The optimization of matching participants, routes, and schedules is widely and actively studied, as shown in Table 5. Several algorithms have been proposed to overcome traditional problems like passenger to driver matching [66] to minimize time and distance to the carpooling starting point and destination [67], to find participants within organizations [68], to determine the pricing schemes for the driver and the passengers [67], and to plan the route by integrating different means such as public transportation or bike rentals with carpooling [69]. Several studies examine the business models framework for services in smart cities.…”
Section: Literature Collection #1mentioning
confidence: 99%
“…The time constraint reflects the time window limitation in the process of vehicle service, and also stipulates the behavior rules of vehicles arriving at the service point in different time periods. The specific constraints are shown as Equation (11) to Equation (13). Equation (11) indicates that the actual arrival time of the taxi should be less than the latest arrival time T j2 requested by the passenger.…”
Section: Time Window Constrainsmentioning
confidence: 99%
“…Zhou et al [12] considered the problem of ride-sharing route and cost sharing, constructed the optimization model with the minimum travel time cost as the objective function, and solved it by Genetic Algorithm. Zhang et al [13] built a multi-objective optimization model for solving the taxi ride-sharing with detour problem and designed a Genetic Algorithm to determine a fair pricing scheme for riders and drivers. In order to optimize the taxi ride-sharing route, Ma et al [14] built the taxi ride-sharing route optimization model with single objective and its extended model with multiple objectives respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Ma and Zhang [12] investigated the impact of di erent shared parking charges and ridesharing payments on tra c ow, and indicated that a scheme with dynamic parking charges and a constant ridesharing payment can signi cantly improve system performance. Zhang et al [13] believed that the key of the taxi carpooling detour scheme is to determine the appropriate payment ratio and detour payment ratio, and a multi-objective optimization model for taxi carpooling detours was established.…”
Section: Introductionmentioning
confidence: 99%